2003
DOI: 10.1038/sj.leu.2403038
|View full text |Cite
|
Sign up to set email alerts
|

Age-related patterns of immunoglobulin and T-cell receptor gene rearrangements in precursor-B-ALL: implications for detection of minimal residual disease

Abstract: Detailed Southern blot and PCR analysis of Ig heavy (IGH), Ig kappa (IGK), T-cell receptor delta (TCRD), and TCR gamma (TCRG) genes were performed in 289 children with precursor-B-ALL in order to determine age-related Ig/TCR patterns and their implications for detection of minimal residual disease (MRD). Overall, IGH, IGK, TCRD, and TCRG gene rearrangements were detected in 98, 62, 90, and 58% of patients, respectively. The frequency of IGH and TCRD rearrangements was independent of rearrangements in one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 63 publications
4
40
2
1
Order By: Relevance
“…18,20,23,24,26,41,42 We demonstrated that infant ALL patients of 0-6 months of age at diagnosis as compared to older infants (6-12 months) showed a more immature Ig/TCR pattern, particularly characterized by a high prevalence of incomplete IGH gene rearrangements and low frequencies of complete IGH, IGK and TCRD gene rearrangements (Figure 4). Infants with MLL-AF4 were more prevalent in the youngest age groups, whereas older infant leukemias more frequently lacked a rearranged MLL gene.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…18,20,23,24,26,41,42 We demonstrated that infant ALL patients of 0-6 months of age at diagnosis as compared to older infants (6-12 months) showed a more immature Ig/TCR pattern, particularly characterized by a high prevalence of incomplete IGH gene rearrangements and low frequencies of complete IGH, IGK and TCRD gene rearrangements (Figure 4). Infants with MLL-AF4 were more prevalent in the youngest age groups, whereas older infant leukemias more frequently lacked a rearranged MLL gene.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Within infant ALL, different Ig/TCR patterns were observed, depending on age of the infant at diagnosis, immunophenotype (CD10 expression) and particularly depending on the presence and type of MLL rearrangement. Immature Ig/TCR gene rearrangements were found in MLL-AF4 and MLL-ENL-positive infant ALL patients, which generally presented at young age (0-6 months) with a CD10-negative ALL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations